2017
DOI: 10.1016/j.bbr.2016.10.048
|View full text |Cite
|
Sign up to set email alerts
|

Motor skill for tool-use is associated with asymmetries in Broca’s area and the motor hand area of the precentral gyrus in chimpanzees ( Pan troglodytes )

Abstract: Among nonhuman primates, chimpanzees are well known for their sophistication and diversity of tool use in both captivity and the wild. The evolution of tool manufacture and use has been proposed as a driving mechanism for the development of increasing brain size, complex cognition and motor skills, as well as the population-level handedness observed in modern humans. Notwithstanding, our understanding of the neurological correlates of tool use in chimpanzees and other primates remains poorly understood. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 88 publications
(78 reference statements)
0
25
0
Order By: Relevance
“…Moreover, the manipulative complexity of extractive foraging seems to intensify during tool use, which requires diverse manual actions combined with strength, precision, bimanually coordinated movements, and more cognitive skills (Heldstab et al, ; Parker & Gibson, ; Resende, Nagy‐Reis, Lacerda, Pagnnota, & Savalli, ). Tool use is considered as a driver for right handedness (e.g., Forrester, Quaresmini, Leavens, Mareschal, & Thomas, ; Frost, ; Hopkins et al, ; Moura, ). Thus, we expected that S. libidinosus , a species that evolved in the dry forests of Brazil (Cerrado & Caatinga, Alfaro, Boubli, et al, ) should be more right handed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the manipulative complexity of extractive foraging seems to intensify during tool use, which requires diverse manual actions combined with strength, precision, bimanually coordinated movements, and more cognitive skills (Heldstab et al, ; Parker & Gibson, ; Resende, Nagy‐Reis, Lacerda, Pagnnota, & Savalli, ). Tool use is considered as a driver for right handedness (e.g., Forrester, Quaresmini, Leavens, Mareschal, & Thomas, ; Frost, ; Hopkins et al, ; Moura, ). Thus, we expected that S. libidinosus , a species that evolved in the dry forests of Brazil (Cerrado & Caatinga, Alfaro, Boubli, et al, ) should be more right handed.…”
Section: Discussionmentioning
confidence: 99%
“…These populations of capuchins spend significantly more time consuming leaves than capuchins from the Caatinga dry forest, which tend to spend more time foraging for mobile prey (Izar et al, ). It is possible that capuchin monkeys from the Atlantic forest evolved under a stronger selective pressure for high reliance on bimanual feeding and extractive foraging, which requires more sequential actions and planning and might put a stronger selective pressure on left hemisphere/right hand use (Cochet & Byrne, ; Hopkins et al, ). Unfortunately, there is no published study on the feeding ecology of S. flavius and detailed data on manipulative and extractive foraging techniques employed by Atlantic forest capuchins is also lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, neuroimaging studies of nonhuman primates have shown that certain hemispheric asymmetries found in human brains are also present in chimpanzees (Gannon, Holloway, Broadfield, & Braun, ; Hopkins et al, ; Lyn et al, ) and Old World monkeys, such as baboons (Marie et al, ) and macaque monkeys (Bogart et al, ). For instance, the left inferior frontal gyrus (IFG) and left planum temporale (PT), which are involved in language production and comprehension skills in human (Bogart et al, ), have been shown larger and deeper than those on the right hemisphere in chimpanzees and baboons (Gannon et al, ; Hopkins, Marino, Rilling, & MacGregor, ; Lyn et al, ; Marie et al, ), similar to the findings in human infants, old children, and adults (Glasel et al, ; Hill et al, ; Li, Nie, Wang, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The tool theory (Forrester, Quaresmini, Leavens, Mareschal, & Thomas, ; Kimura, ) states that manual specialization when using tools, and more broadly in manipulative actions, is related to the necessary hemispheric lateralization to support language functions. However, neuroanatomical investigations revealed contrasting results (Balzeau, Gilissen, Holloway, Prima, & Grimaud‐Hervé, ; Hopkins & Cantalupo, ; Hopkins et al, ). Around 63% of strong left‐handers had after all a dominant left‐hemisphere for language (Knecht et al, ).…”
Section: Introductionmentioning
confidence: 99%